Caracterización fisicoquímica y cromatográfica del aceite esencial de Eucharis amazonica (L) Linden ex Planch - Pérez Gonzales, Jaime Martín (2022)
The objective of the work was oriented to characterize the essential oil extracted from the flowers of Eucharis amazonica (L) Linden Ex. Planch. Amaryllidaceae family with Petroleum ether, the characterization was carried out by measuring its physicochemical parameters of density, refractive index, solubility and colorful reactions and by high resolution gas chromatographic analysis the number of components. the results were as follows, density 0.8659 g / cm3, refractive index 1.463, the colored reactions were positive for alcohols and ketones. The chromatogram revealed the presence of 10 components: 2 monoterpenes, 3 sesquiterpenes, 1 cyclic hydrocarbon, 3 arenes of phthalic acid and a fatty acid. In addition, the components with the highest abundance are monkeys and sesquiterpenes, which represent 77.7% of the total. The presence of these components suggests that E. amazonica oil can be used primarily in the perfume industry, but also in the cosmetic industry.